Conservation of nucleotide sequences for molecular diagnosis of Middle East respiratory syndrome coronavirus, 2015. (November 2015) - Furuse, Yuki; Okamoto, Michiko; Oshitani, Hitoshi
Highlights: Protocols for the laboratory diagnosis of Middle East respiratory syndrome coronavirus (MERS-CoV) were developed in 2012. Nucleotide sequences of the viruses detected between 2012 and 2015 were analyzed. Mismatches between the sequences of primers/probes and viruses were found. Such mismatches could lead to a lower sensitivity of the assay. Summary: Infection due to the Middle East respiratory syndrome coronavirus (MERS-CoV) is widespread. The present study was performed to assess the protocols used for the molecular diagnosis of MERS-CoV by analyzing the nucleotide sequences of viruses detected between 2012 and 2015, including sequences from the large outbreak in eastern Asia in 2015. Although the diagnostic protocols were established only 2 years ago, mismatches between the sequences of primers/probes and viruses were found for several of the assays. Such mismatches could lead to a lower sensitivity of the assay, thereby leading to false-negative diagnosis. A slight modification in the primer design is suggested. Protocols for the molecular diagnosis of viral infections should be reviewed regularly after they are established, particularly for viruses that pose a great threat to public health such as MERS-CoV.